Building the next model for intervention and turnaround in poorly performing local authorities in England. Issue 5 (2nd September 2016) - Murphy, Peter; Jones, Martin
ABSTRACT: This paper examines the design and implementation of the two recent models or strategies adopted for the intervention and turnaround of poorly performing local authorities in England in the two distinct periods of 2002–2008 and 2011–2015. The first was integral to the Comprehensive Performance Management regimes, while the second was developed under the Sector Led Improvement regime. The intention is not to determine which regime has, or had, the most merit or inadequacies, but rather to synthesise knowledge and identify areas that could be improved as policy and practice moves forward, particularly in the light of the recent general election in the UK. The paper finds that both models have merits as well as weaknesses, dependent upon context and policy priorities. It provides a review of when and where alternative models should be used, and a contribution to the development of the next regime. This, the authors contend, should have a greater emphasis on achieving more appropriate levels of public assurance than the current model is providing.